Empirical research on the experience of the New Homiletic in South Korea - Park, Hyun W.; Wepener, Cas (Verbum et ecclesia, 2016)
The purpose of this article is to present empirical research to reveal the reality of the New Homiletic in South Korea. This research was conducted by means of semistructured interviews with seven pastors and eight laypeople of the evangelical faith, residing in Seoul and its metropolitan areas, within the age limits of 20 59 years. The aim was to uncover the experience of the sermons by both the preachers and the hearers of the sermons. The researcher chose Pieterse s methodology of analysing the data, which is an inductive analysis called open coding. Six main categories from the pastor s group and five categories from the laypeople emerged from the data. The categories were rearranged into four themes, which is a valuable finding for current-day Korean preaching in order to enhance the homiletical praxis.Intradisciplinary and/or interdisciplinary implications: This article presents empirical research on the reality of the New Homiletic in South Korea. The results indicate similarity between South Korea and the USA. The conclusion is that traditional discourse should give way to the New Homiletic. This research can become the basis for finding new strategies for evangelical preaching.Keywods: Preaching; South Korean church; Empirical research; New Homiletic